Reduction of Ripples in A Three Phase Dc-Dc Converter Using Pi Controller - N, Padmini.; Anupama Prakash, Dr. (International Journal of Engineering and Technology, 2018)
The increasing population which in leads to the increase in use of automobiles which constitutes to seventy five percent of carbon monoxide emission. The use of electrical vehicles (EV) has become a necessity to protect the environment from further pollution. The slow charging of the EV is a main hindrance for the success of EV. Fast charging can be achieved by providing charging locations that can be built which can charge the EV in short time span. This paper proposes a bidirectional DC-DC converter with six inverter legs in parallel which is similar to 3Î¦ dual active bridge (DAB) converter. This proposed converter has additional inverter legs which increases the converter current capacity resulting in fast charging. A feedback controller is implemented to reduce the ripple content.Â